In vivo Experience With NRT to Increase Adherence and Smoking Abstinence Among Individuals in the Criminal Legal System: Study Protocol for a Randomized Clinical Trial - Hawes, Elizabeth S.; Mildrum Chana, Sofía; Faust, Alexandra; Baker, Julianne C.; Hendricks, Peter S.; Azuero, Andres; Lahti, Adrienne C.; Carpenter, Matthew J.; Cropsey, Karen L. (Frontiers in Psychiatry, 2022)
Background: While tobacco use among individuals involved in the criminal legal system remains 3-4 times higher than the general population, few interventions have been targeted for this population to aid in smoking cessation. Nicotine replacement therapy (NRT) is a relatively effective and accessible smoking cessation aid; however, individuals frequently stop use of NRT early due to side effects and misperceptions about the products. The present study aims to address low medication adherence by examining the efficacy of an “in vivo” NRT sampling experience in individuals under community criminal legal supervision. Methods: Following recruitment through community legal outlets, participants (N=517) are randomized to either an “in vivo NRT sampling” group or a standard smoking cessation behavioral counseling group. The in vivo group uses NRT in session and discusses perceptions and experiences of using NRT in real time while the standard smoking cessation counseling group receives four sessions of standard behavioral smoking cessation counseling. Both groups receive four intervention sessions and twelve weeks of NRT following the intervention. The 6-month post-intervention primary outcome measures are smoking point-prevalence abstinence and medication adherence. Conclusion: This is a novel smoking cessation intervention specifically aimed at increasing NRT adherence and smoking cessation among those involved in the criminal legal system, a group of individuals with high smoking rates and low rates of pharmacotherapy use. If proven effective, the present treatment could be a novel intervention to implement in criminal legal settings given the minimal requirement of resources and training.